Erratum - BRAGA, Vanessa Torres; OLIVEIRA, Marcelo de; FERNANDES, Dayane Stéphanie; FILIÚ, Wander Fernando de Oliveira; CAVALHEIRO, Leandro Fontoura; NAZÁRIO, Carlos Eduardo Domingues; VARGAS, Márcio Olivio Figueiredo; ASATO, Marcel Arakaki; MENEZES, Adriana Conceicon Guércio; FRAZÍLIO, Maria Paula Ferreira Fialho; NASCIMENTO, Valter Aragão do; SANTANA, Lidiani Figueiredo; et al. (Food Science and Technology, 2024)
***